The effect of 5A nursing combined with psychological nursing on the immune function, cancer-related fatigue and complications of patients undergoing radical resection of colorectal cancer - Xu, Yun; Yang, Juan (Cellular and Molecular Biology, 2022)
This study aimed to analyze the effects of 5A nursing (including Ask, Assess, Advise, Assist, and Access) combined with psychological nursing on the immune function, cancer-related fatigue, and complications of patients undergoing radical resection of colorectal cancer. For this purpose, 64 patients undergoing radical resection of colorectal cancer were treated with nursing intervention during the perioperative period from March 2019 to March 2021. They were randomly divided into a control group and a study group according to admission order. Each group had 32 cases. The control group performed routine nursing, and 5A nursing combined with psychological nursing was performed on the research group. Then the immune function, cancer-related fatigue, complications, self-efficacy, and nursing satisfaction were compared between the two groups. Results showed that the levels of CD3+ and CD4+ in the two groups were lower than before nursing, and the levels of CD8+, IgA, IgM, and IgG were higher than before nursing (P<0.05). The reduction of CD3+ and CD4+ in the study group was less than the control group, and the increase of CD8+, IgA, IgM, and IgG in the study group was higher than the control group (P<0.05). The scores of cancer-related fatigue after nursing were lower than before nursing (P<0.05), and the reduction of cancer-related fatigue in the study group was higher than the control group (P<0.05). The incidence of postoperative complications in the study group (12.50%) was lower than the control group (25.00%) after nursing (p<0.05). The scores of all dimensions of self-efficacy of the two groups after nursing were higher than before nursing (P<0.05). The improvement of self-efficacy of the study group was better than the control group (P<0.05). The overall nursing satisfaction of the observation group after nursing (96.88%) was higher than the control group (84.38%)(P<0.05). According to the results, the use of 5A nursing combined with psychological nursing can effectively relieve the perioperative psychological pressure of the patients, improve the immune function of the body, relieve cancer-related fatigue, prevent and control the incidence of complications, and improve the quality of clinical life of the patients for patients undergoing radical resection of colorectal cancer.